Preparation method and application of conductive anti-corrosion coating for magnesium alloy bipolar plate
By preparing conductive anti-corrosion coating on magnesium alloy bipolar plates, the problems of magnesium alloy bipolar plates are solved, and the problems of corrosion resistance and conductivity are reduced in fuel cell environments are achieved, which achieves higher corrosion resistance and conductivity, and extends the use Lifespan and reduce costs.
Patent Information
- Application Number
- CN202211617308.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-15
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2042-12-15
AI Technical Summary
The magnesium alloy bipolar plate is prone to form a passivation film and an oxide layer in the working environment of a fuel cell, resulting in reduced conductivity and corrosion, making it difficult to work stably, and has a high cost.
Conductive anticorrosion coatings are prepared by materials such as conductive polymers, adhesives and nanooxides. The coating is uniformly coated on the surface of magnesium alloy through ultrasonic dispersion and spin coating technology to form a corrosion-resistant layer.
It improves the corrosion resistance and conductivity of magnesium alloy bipolar plates, extends the service life of the bipolar plates, reduces costs, and meets the lightweight demand of proton exchange membrane fuel cells.
Smart Images

Figure CN116239906B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of surface treatment, and in particular to a preparation method of a conductive anti-corrosion coating for a magnesium alloy bipolar plate and application thereof. Background Art
[0002] In recent years, the energy depletion and environmental pollution caused by the extensive use of fossil energy have become increasingly serious. Fuel cells are a power generation device that can directly convert non-polluting fuels such as hydrogen into electrical energy through chemical energy. Hydrogen energy has been increasingly used as a substitute for fossil fuels. Fuel cells do not use internal combustion engines, have no noise or vibration, can not only achieve efficient energy conversion, but also produce almost no pollutants. They have become the focus of new energy technology.
[0003] Proton exchange membrane fuel cells (PEMFCs) are widely used in transportation, power stations, mobile power supplies, military fuel cells and other fields due to their advantages such as high energy conversion rate, fast startup, low noise, environmental friendliness, low operating temperature and long operating life.
[0004] As one of the key components in proton exchange membrane water electrolysis to produce hydrogen, the bipolar plate provides a place for gas reaction, collects current, supports membrane electrodes, and manages water. The bipolar plate is required to have comprehensive properties such as high corrosion resistance, low interface resistivity, good mechanical strength, hydrophobicity and anti-oxidation. The corresponding materials for preparing the bipolar plates should have good electrical conductivity, thermal conductivity, corrosion resistance, gas impermeability and mechanical strength.
[0005] The current bipolar plate materials mainly include graphite materials, composite materials and metal materials. Graphite bipolar plates have some obvious disadvantages: such as low mechanical strength, complex manufacturing process, high volume power density, etc. These disadvantages greatly restrict the application of graphite bipolar plates in proton membrane exchange membrane fuel cells; composite bipolar plates have simple manufacturing process and strong corrosion resistance, but poor conductivity; compared with graphite bipolar plates, metal bipolar plates have the advantages of low cost, easy manufacturing, high power density and good mechanical properties, which are suitable for mass production. They are the preferred electrode plate material for the industrialization of fuel cells.
[0006] Bipolar plates account for 80% of the volume, 70% of the mass and 29% of the cost of the fuel cell stack. Developing low-density metal bipolar plates to prepare lightweight fuel cells has become a trend in the future development of fuel cells. The bipolar plates made of metal materials such as aluminum, nickel, titanium and stainless steel currently used have high density and high cost, which can hardly meet the needs of lightweight fuel cells. Summary of the invention
[0007] In order to improve the deficiencies of the prior art, the present invention provides a method for preparing a conductive anti-corrosion coating for a magnesium alloy bipolar plate. From the perspective of lightweight, a magnesium alloy is selected as a substrate. In a battery working environment, the magnesium alloy not only forms a passivation film on the surface, causing high surface resistance, but is also easily oxidized, resulting in a decrease in the conductivity of the battery. The oxidized and corroded magnesium alloy bipolar plate is difficult to work stably and needs to be replaced in a serious case, resulting in a decrease in the conductivity of the fuel cell, low stability in use, and high cost. Therefore, magnesium alloy is currently only in the theoretical stage as a bipolar plate material.
[0008] The first object of the present invention is to provide a method for preparing a conductive anti-corrosion coating for a magnesium alloy bipolar plate, the method comprising the following steps:
[0009] S1, mixing a conductive polymer, an adhesive and an organic solvent to obtain a coating;
[0010] S2. Apply the paint on the surface of the magnesium alloy to form a coating.
[0011] According to an embodiment of the present invention, the step S1 comprises the following steps: adding a binder to the conductive high molecular polymer and grinding until the mixture is uniformly mixed, adding an organic solvent, mixing and dispersing the mixture, and obtaining a coating.
[0012] According to an embodiment of the present invention, the dispersion of the conductive high molecular polymer and the binder in the organic solvent is performed by stirring and / or ultrasound, for example, by ultrasound.
[0013] According to an embodiment of the present invention, the ultrasonic time is 10-30 hours, preferably the ultrasonic time is 15-25 hours.
[0014] According to an embodiment of the present invention, the step S1 comprises the following steps: firstly dissolving the adhesive in a part of the organic solvent, then adding the adhesive into the conductive high molecular polymer and another part of the organic solvent, mixing and dispersing the mixture, and obtaining the coating.
[0015] According to an embodiment of the present invention, the conductive high molecular polymer is at least one selected from polyaniline, polypyrrole and polythiophene, for example, polyaniline.
[0016] According to an embodiment of the present invention, the particle size of the conductive high molecular polymer is 100-500 nanometers, and preferably the particle size of the conductive high molecular polymer is 200-400 nanometers.
[0017] According to an embodiment of the present invention, the mass ratio of the conductive polymer to the adhesive is 1:(0.1-0.3), preferably the mass ratio of the conductive polymer to the adhesive is 1:(0.15-0.25), for example, the mass ratio of the conductive polymer to the adhesive is 1:0.1, 1:0.13, 1:0.15, 1:0.18, 1:0.20, 1:0.22, 1:0.25, 1:0.28, 1:0.3, or any value in the middle of any two points.
[0018] According to an embodiment of the present invention, the binder is selected from at least one of polyvinylidene fluoride, polyacrylonitrile, polyethersulfone, vinyl acetate copolymer, and polyethylene terephthalate. Preferably, the binder is selected from polyvinylidene fluoride or polyacrylonitrile.
[0019] According to an embodiment of the present invention, the organic solvent is selected from at least one of xylene, N-methylpyrrolidone, tetrahydrofuran, and dimethylformamide. For example, the organic solvent is selected from N-methylpyrrolidone.
[0020] According to an embodiment of the present invention, the mass volume ratio of the conductive polymer to the organic solvent is 1:(3-10) g / mL, and the mass volume ratio of the conductive polymer to the organic solvent is 1:(4-8) g / mL, for example, the mass volume ratio of the conductive polymer to the organic solvent is 1:5 g / mL.
[0021] According to an embodiment of the present invention, step S1 further includes the following steps: adding a binder and a corrosion inhibitor to the conductive high molecular polymer, grinding until the mixture is uniformly mixed, adding an organic solvent to mix and disperse the mixture, and obtaining a coating.
[0022] According to an embodiment of the present invention, step S1 further includes the following steps: firstly dissolving the adhesive in a part of the organic solvent, and then adding the conductive polymer, the corrosion inhibitor and another part of the organic solvent to mix and disperse to obtain the coating.
[0023] According to an embodiment of the present invention, the corrosion inhibitor comprises nano oxides, and the nano oxides are selected from SiO 2 , ZnO, TiO 2 、TiN、MnO 2 At least one of, for example, SiO 2 、TiO 2 .
[0024] According to an embodiment of the present invention, the nano-oxide is spherical, flake-shaped, fibrous or irregular nanoparticles.
[0025] According to an embodiment of the present invention, the particle size of the nano oxide is 15-60 nanometers, preferably the particle size of the nano oxide is 20-40 nanometers. According to an embodiment of the present invention, the amount of the corrosion inhibitor added is 0.5% to 3.0% of the mass sum of the polyaniline and the binder, preferably the amount of the corrosion inhibitor added is 1.0% to 2.0% of the mass sum of the polyaniline and the binder, for example, any value among 0.8%, 1.0%, 1.2%, 1.4%, 1.6%, 1.8%, 2.0%, 2.5%, 2.8%, or any value in the intermediate value formed by any two point values.
[0026] According to an embodiment of the present invention, the following step is further included before step S1: grinding the surface of the magnesium alloy to a rough surface.
[0027] According to an embodiment of the present invention, the polishing includes using sandpaper to polish the surface of the magnesium alloy to a mesh size of 800 to 1500.
[0028] Preferably, the polishing includes polishing the magnesium alloy surface with sandpaper of increasing mesh size in sequence until the surface is 800-1500 mesh, for example, polishing the magnesium alloy surface with SiC sandpaper of 180 mesh, 400 mesh, 800 mesh, and 1200 mesh in sequence.
[0029] According to an embodiment of the present invention, after polishing, the step of cleaning and drying the surface of the magnesium alloy is also included.
[0030] According to an embodiment of the present invention, the cleaning includes cleaning with anhydrous ethanol and deionized water in sequence, for example, first ultrasonic cleaning with anhydrous ethanol and then rinsing with deionized water.
[0031] According to an embodiment of the present invention, the time of ultrasonic cleaning with anhydrous ethanol is 3 to 15 minutes.
[0032] According to the implementation scheme of the present invention, step S2 includes the following steps: placing the pretreated magnesium alloy on the turntable of the coating machine, using a pipette to absorb an appropriate amount of the coating dispersed in step 2 and adding it dropwise to the middle of the magnesium alloy, starting spin coating to prepare the coating, and after the spin coating is completed, taking it out and placing it in a vacuum drying oven for low-temperature drying.
[0033] According to an embodiment of the present invention, the magnesium alloy has a length of 10 to 40 mm, a width of 10 to 40 mm, and a height of 2 to 10 mm.
[0034] According to an embodiment of the present invention, in step S2, the spin coating temperature is 5-25°C, the rotation speed is 500-1500 rpm, and the acceleration is 300-600 m / s 2 , the spin coating time is 5 to 20 seconds.
[0035] A second object of the present invention is to provide a magnesium alloy bipolar plate for a proton exchange membrane fuel cell, wherein the surface of the magnesium alloy bipolar plate has the conductive anti-corrosion coating as described above.
[0036] According to an embodiment of the present invention, the thickness of the conductive anti-corrosion coating is 8 to 15 micrometers, and preferably the thickness of the conductive anti-corrosion coating is 10 to 12 micrometers.
[0037] According to an embodiment of the present invention, the conductive anti-corrosion coating has substantially Figure 1 Actual picture shown.
[0038] According to an embodiment of the present invention, the conductive anti-corrosion coating has substantially Figure 2 Scanning electron micrograph shown.
[0039] According to an embodiment of the present invention, the magnesium alloy bipolar plate with a conductive anti-corrosion coating has substantially the following Figure 3 The potentiodynamic polarization curve is shown.
[0040] The third object of the present invention is to provide a proton exchange membrane fuel cell having a plurality of magnesium alloy bipolar plates as described above.
[0041] Beneficial Effects
[0042] 1) The present invention uses a magnesium alloy with extremely low density as a substrate, and arranges a corrosion-resistant coating on the surface of the substrate. The corrosion-resistant coating uses a conductive polymer such as polyaniline as a matrix material. Polyaniline has corrosion inhibition behavior and anion exchange properties. It can protect the underlying metal substrate (magnesium alloy) while being able to exchange anions with chloride ions in a corrosive environment to inhibit the penetration of corrosive anions. At the same time, not only is an adhesive added to enhance the bonding strength between the polyaniline coating and the magnesium alloy and to bond the polyaniline particles, but nano-oxides are also added as corrosion inhibitors to further improve the corrosion resistance of the coating.
[0043] 2) The preparation method of the present invention directly disperses and / or dissolves a conductive polymer and an adhesive in an organic solvent at room temperature to form a coating, and directly applies it on the surface of a magnesium alloy to form a corrosion-resistant layer. The preparation process is simple, the operation steps are few, and it is safe and environmentally friendly, which enhances the industrial application of the coating. The prepared corrosion-resistant layer can reduce the interface contact resistance of the bipolar plate surface and enhance the corrosion resistance. The magnesium alloy bipolar plate coated with the corrosion-resistant layer can meet the requirements of proton exchange membrane fuel cells. Compared with existing metal materials such as aluminum, nickel, titanium and stainless steel, it can greatly reduce the weight of proton exchange membrane fuel cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 This is a physical picture of the magnesium alloy conductive anti-corrosion bipolar plate prepared in Example 1 of the present invention;
[0045] Figure 2 This is a scanning electron microscope image of the magnesium alloy conductive anti-corrosion bipolar plate prepared in Example 1 of the present invention;
[0046] Figure 3 It is a comparison diagram of the potentiodynamic polarization curves of the magnesium alloy conductive anti-corrosion bipolar plate and PANI-AZ31 prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0047] The following will further describe the anti-corrosion coating of the present invention and its preparation method and application in combination with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be interpreted as limiting the scope of protection of the present invention. All technologies realized based on the above content of the present invention are included in the scope of protection of the present invention.
[0048] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.
[0049] The particle size of the polyaniline used in the following examples is 100 to 500 nm.
[0050] Example 1
[0051] A method for preparing a conductive anti-corrosion coating for a magnesium alloy bipolar plate of a proton exchange membrane fuel cell comprises the following steps:
[0052] 1) Substrate pretreatment
[0053] AZ31 magnesium alloy with a size of 40 mm × 40 mm × 5 mm was used as the substrate, and was polished step by step with 180 mesh, 400 mesh, 800 mesh, and 1200 mesh SiC sandpaper until the surface was smooth and flat. After polishing, it was ultrasonicated with anhydrous ethanol for 5 minutes, washed with deionized water, and dried;
[0054] 2) Coating preparation
[0055] 0.6 g of polyaniline and 0.1 g of polyvinylidene fluoride were weighed and ground in a mortar for 20 minutes until the solid coating was physically mixed evenly, where even mixing means that there were no visible white polyvinylidene fluoride particles in the mixture, and then 3 ml of N-methylpyrrolidone was added dropwise, stirred until the mixture was evenly mixed, and ultrasonically dispersed for 3.5 hours to obtain coating 1;
[0056] 3) Spin coating to prepare the coating
[0057] Set the spin coating temperature to 20 °C, the speed to 1000 rpm, and the acceleration to 500 m / s. 2 , the reaction time is 10s. Take 1ml of coating and add it dropwise in the middle of the magnesium alloy, start spin coating, and put it into a vacuum drying oven after spin coating to remove a small amount of bubbles on the surface and dry it.
[0058] See also Figure 1 It can be seen that the magnesium alloy with the anti-corrosion coating prepared in this embodiment has a uniform distribution of the anti-corrosion coating and is gray-blue in color from a macroscopic point of view.
[0059] See also Figure 2 It can be seen that the anti-corrosion coating prepared in this embodiment has a relatively uniform and dense surface and contains particles from a microscopic point of view.
[0060] Example 2
[0061] A method for preparing a conductive anti-corrosion coating for a magnesium alloy bipolar plate of a proton exchange membrane fuel cell comprises the following steps:
[0062] 1) Substrate pretreatment
[0063] This step is the same as step 1) in Example 1;
[0064] 2) Coating preparation
[0065] 0.5 g of polyaniline and 0.1 g of polyvinylidene fluoride were weighed and ground in a mortar for 20 minutes until the solid coating was physically mixed evenly. Evenly mixed means that there are no white polyvinylidene fluoride particles visible to the naked eye in the mixture. Then 2.5 ml of N-methylpyrrolidone was added and stirred until the mixture was evenly mixed. Ultrasonic dispersion was performed for 5 hours to obtain coating 2.
[0066] 3) Spin coating
[0067] Set the spin coating temperature to 20 °C, the speed to 800 rpm, and the acceleration to 500 m / s. 2 , the reaction time is 15s. Take 1ml of coating and add 2 drops to the middle of the magnesium alloy, start spin coating, and put it into a vacuum drying oven after spin coating to remove a small amount of bubbles on the surface and dry it.
[0068] Example 3
[0069] A method for preparing a conductive anti-corrosion coating for a magnesium alloy bipolar plate of a proton exchange membrane fuel cell comprises the following steps:
[0070] 1) Substrate pretreatment
[0071] The steps are the same as step 1 of Example 1;
[0072] 2) Coating preparation
[0073] 0.6 g of polyaniline and 0.1 g of polyvinylidene fluoride were weighed and ground in a mortar for 20 minutes until the solid coating was physically mixed evenly, where even mixing means that no white particles of polyvinylidene fluoride were visible to the naked eye. Then 3 ml of xylene was added and stirred until the mixture was evenly mixed, and ultrasonic dispersion was performed for 3.5 hours to obtain coating 3.
[0074] 3) Spin coating
[0075] Set the spin coating temperature to 20 °C, the speed to 1000 rpm, and the acceleration to 500 m / s. 2 , the reaction time is 15s, take 1ml of coating and add 3 drops in the middle of the magnesium alloy, start spin coating, and put it into a vacuum drying oven after spin coating to remove a small amount of bubbles on the surface and dry it.
[0076] Example 4
[0077] A method for preparing a conductive anti-corrosion coating for a magnesium alloy bipolar plate of a proton exchange membrane fuel cell comprises the following steps:
[0078] 1) Substrate pretreatment
[0079] This step is the same as step 1 of Example 1;
[0080] 2) Coating preparation
[0081] Weigh 0.6g polyaniline and 0.1g polyvinylidene fluoride, add 1.5% TiO 2 First, grind in a mortar for 20 minutes until the solid coating is physically mixed evenly, where even mixing means that there are no visible white polyvinylidene fluoride particles in the mixture, then add 3 ml of N-methylpyrrolidone, stir until the mixture is evenly mixed, and ultrasonically disperse for 3.5 hours to obtain coating 4;
[0082] 3) Spin coating to prepare the coating
[0083] Set the spin coating temperature to 20 °C, the speed to 1000 rpm, and the acceleration to 500 m / s. 2 , the reaction time is 10s. Take 1ml of coating and add 4 drops to the middle of the magnesium alloy, start spin coating, and put it into a vacuum drying oven after spin coating to remove a small amount of bubbles on the surface and dry it.
[0084] It is worth noting that the contents not described in detail in the embodiments of the present invention belong to the prior art known to professional and technical personnel in the field.
[0085] Application Example 1
[0086] The potential scanning test was carried out using Wuhan Corrtest CS350 electrochemical workstation, and a three-electrode system was used: the sample was used as the working electrode (see Figure 3 As shown, the samples include AZ31 and PANI-AZ31, AZ31 refers to the AZ31 magnesium alloy sample with an anti-corrosion layer prepared in Example 1, and PANI-AZ31 refers to the sample coated with a polyaniline coating on an AZ31 substrate), Ag / AgCl electrode is used as a reference electrode, platinum mesh is used as an auxiliary electrode, 3.5wt.% NaCl solution is selected as the corrosive medium, and the test area is 1cm 2After the sample was immersed in the corrosive medium until the open circuit potential was stable, a dynamic potential scanning test was performed. The dynamic potential scanning range was -0.5 to 0.5 V relative to the open circuit potential, and the scanning rate was 1 mV / s.
[0087] See also Figure 3 It can be seen that the AZ31 magnesium alloy sample with an anti-corrosion layer prepared in Example 1 ( Figure 3 Compared with the left curve in the middle), the PANI-AZ31 sample ( Figure 3 The right side curve in the middle corresponds to the positive shift of the self-corrosion potential and the decrease of the self-corrosion current density, which indicates that the anti-corrosion coating prepared in Example 1 can improve the corrosion resistance of the AZ31 substrate.
[0088] The results show that the self-corrosion current density of AZ31 magnesium alloy sample is 2.667×10 -5 Ω / cm 2 , the self-corrosion potential is -1.567V, the corrosion rate is 0.576mm / a; the self-corrosion current density of PANI-AZ31 sample is 1.803×10 -6 Ω / cm 2 , the self-corrosion potential is -0.314V, and the corrosion rate is 0.039mm / a. It can be seen that the coating prepared by the method of the present invention not only has good bonding with the magnesium alloy, but also has excellent corrosion resistance and good electrical conductivity. The preparation steps of the anti-corrosion coating of the present invention are simple and the reaction conditions are easy to control.
[0089] The above examples are used to illustrate the specific implementation of the present invention. However, the protection scope of the present invention is not limited to the above exemplary implementation. Any modification, equivalent substitution, improvement, etc. made by those skilled in the art within the spirit and principle of the present invention shall be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a conductive anti-corrosion coating for a magnesium alloy bipolar plate, characterized in that: The method comprises the following steps: S1. Mixing a conductive polymer, a binder and an organic solvent to obtain a coating, wherein the conductive polymer is selected from polyaniline, the binder is selected from polyvinylidene fluoride, the mass ratio of the conductive polymer to the binder is 1:(0.1-0.3), and the mass volume ratio of the conductive polymer to the organic solvent is 1:(3-10) g / mL; S2. Apply the coating on the surface of the magnesium alloy to form a coating: place the pretreated magnesium alloy on the turntable of the coating machine, use a pipette to absorb an appropriate amount of the coating dispersed in step 2 and add it dropwise to the middle of the magnesium alloy, and start spin coating to prepare the coating. After the spin coating is completed, take it out and place it in a vacuum drying oven for low-temperature drying.
2. The method for preparing a conductive anti-corrosion coating for a magnesium alloy bipolar plate according to claim 1, characterized in that: The step S1 comprises the following steps: adding an adhesive to the conductive high molecular polymer and grinding until the mixture is uniformly mixed, adding an organic solvent, mixing and dispersing the mixture, and obtaining a coating.
3. The method for preparing a conductive anti-corrosion coating for a magnesium alloy bipolar plate according to claim 1, characterized in that: The step S1 comprises the following steps: firstly dissolving the adhesive in a part of the organic solvent, then adding the adhesive into the conductive high molecular polymer and another part of the organic solvent, mixing and dispersing the mixture, and obtaining the coating.
4. The method for preparing a conductive anti-corrosion coating for a magnesium alloy bipolar plate according to claim 1, characterized in that: The conductive high molecular polymer and the adhesive are dispersed in the organic solvent by stirring and / or ultrasound, and the ultrasound time is 10-30 hours, and the ultrasound time is 15-25 hours.
5. The method for preparing a conductive anti-corrosion coating for a magnesium alloy bipolar plate according to claim 1, characterized in that: The particle size of the conductive high molecular polymer is in the range of 100-500 nanometers.
6. The method for preparing a conductive anti-corrosion coating for a magnesium alloy bipolar plate according to any one of claims 1 to 4, characterized in that: The mass ratio of the conductive high molecular polymer to the adhesive is 1:(0.15-0.25).
7. The method for preparing a conductive anti-corrosion coating for a magnesium alloy bipolar plate according to any one of claims 1 to 4, characterized in that: The organic solvent is selected from at least one of xylene, N-methylpyrrolidone, tetrahydrofuran and dimethylformamide.
8. The method for preparing a conductive anti-corrosion coating for a magnesium alloy bipolar plate according to any one of claims 1 to 4, characterized in that: Before step S1, the following step is also included: grinding the surface of the magnesium alloy to a rough surface.
9. The method for preparing a conductive anti-corrosion coating for a magnesium alloy bipolar plate according to claim 8, characterized in that: The sandpaper used for grinding is 800-1500 mesh sandpaper.
10. The method for preparing a conductive anti-corrosion coating for a magnesium alloy bipolar plate according to any one of claims 1 to 4, characterized in that: In step S2, the spin coating temperature is 5-25°C, the rotation speed is 500-1500 rpm, and the acceleration is 300-600 m / s. 2 , the spin coating time is 5 to 20 s.
11. A magnesium alloy bipolar plate for a proton exchange membrane fuel cell, characterized in that: The surface of the magnesium alloy bipolar plate has a conductive anti-corrosion coating prepared by the method described in any one of claims 1 to 10.
12. The magnesium alloy bipolar plate according to claim 11, characterized in that: The thickness of the conductive anti-corrosion coating is 8 to 15 microns.
13. A proton exchange membrane fuel cell, characterized in that: The fuel cell has a plurality of magnesium alloy bipolar plates as claimed in claim 11 or 12.
Citation Information
Patent Citations
Conductive composition containing polyvinylidene fluoride and battery using the composition
JP1994124708A
Cited By
Fuel cell stainless steel bipolar plate and preparation method thereof
CN119208644B
A corrosion-resistant coating for metal bipolar plate and preparation method thereof
CN119221060B